Antibacterial gauzes are effective in preventing infections after percutaneous endoscopic gastrostomy placement: a retrospective analysis. Issue 3 (March 2016) - Strijbos, Denise; Schoon, Erik J.; Curvers, Wouter; Friederich, Pieter; Flink, Hajo J.; Stronkhorst, Arnold; Gilissen, Lennard P.L.
Abstract : Objectives: The most common complication after percutaneous endoscopic gastrostomy (PEG) placement is peristomal wound infection (up to 40% without antibiotic prophylaxis). Single-dose parenteral prophylactic antibiotics as advised by current guidelines decrease the infection rate to 9–15%. We assume a prolonged effect of local antibiotic treatment with antibacterial gauzes. This study is the first to describe the effect of antibacterial gauzes in preventing infections in PEG without the use of antibiotics. Methods: A retrospective data analysis was carried out of all patients with PEG insertion between January 2009 and October 2014 in the Catharina Hospital Eindhoven. Data include placement and the period of the first 2 weeks after PEG placement, and long-term follow-up. All patients received a locally applied antibacterial gauze polyhexamethylene biguanide immediately following PEG insertion for 3 days. No other antibiotics were administered. The main outcomes were wound infection, peritonitis, and necrotizing fasciitis; secondary outcomes included other complications. Results: A total of 331 patients with only antibacterial gauzes were analyzed. The total number of infections 2 weeks after PEG insertion was 9.4%, including 8.2% minor and 1.2% major infections (peritonitis). No wound infection-related mortality or bacterial resistance was found. Costs are five times lower than antibiotics, and gauzes are more practical and patient friendly for use. Conclusion: Retrospectively, antibacterial gauzes are at least comparable with literature data on parenteral antibiotics in preventing peristomal wound infection after PEG placement, with an infection rate of 9.4%. Rates of other complications found in this study were comparable with current literature data.